The effects of beta-alanine supplementation and regular taekwondo training on anaerobic and aerobic performance in female taekwondo athletes - Elaheh Dianati; Hamid Rajabi; Nena Khaledi; Sadegh Amani Shalamzari (Shahid Beheshti University, 2024)
Background and Purpose: Beta-alanine supplement, which is a precursor of carnosine, may improve performance by providing a buffering effect. The purpose of this study was to investigate the effect of beta-alanine supplementation and regular Taekwondo training on anaerobic, aerobic, and endurance activity substrate metabolism in female Taekwondo athletes.Materials and Methods: Twenty-four female professional taekwondo practitioners (age, 18.0±2.5 years), from Tehran province volunteered to participate in this research. Based on the body composition and training history, the subjects were divided into two groups (n=12) of supplement and placebo. The pre-tests consisted of the an aerobic specific test (Progressive Specific Taekwondo Test, PSTT) including repeated strikes of Bandal-Tchagui to exhaustion time during a maximum duration of 15 minutes and a taekwondo anaerobic test (Frequency Speed of Kick Te, FSKT) including 5 sets of 10-second high-speed Bandal-Tchagui kicks with maximum strength. Furthermore, the substrate metabolism of the endurance activity was measured by a gas analyzer, and the VCO2, VO2, VO2peak, HR, and HRpeak were measured. During and immediately after the test, the level of perception of fatigue was evaluated. Moreover, blood lactate levels were measured using a lactometer after the anaerobic and aerobic tests. After 28 days of receiving the supplement or placebo (5g/day) at the designated day times, the pre-test measurements were repeated. Repeated measures of ANOVA with between-group factor and Bonferroni post-hoc tests were used to compare the data.Results: There was no significant difference between the two supplement and placebo groups for anaerobic capacity, aerobic capacity, and substrate metabolism (p<0.05). Although, both groups (supplement and placebo) showed significant improvements in the time to exhaustion and the number of steps to exhaustion in the post-test compared to the pre-test, these improvements were significantly higher in the supplement group compared to the placebo (p<0.05).Conclusion: During the research period, beta-alanine supplementation had only an effect on some performance indicators and probably more pronounced effects on the performance of elite athletes would be seen in the long term. However, this little gain can be important in professional athletes, and more studies are needed in this field for a concrete conclusion.